Interconnection of Self-actualization of Women with Different Marital Status and Indicators of Family Crisis State - Falyova, Olena (Psychological Prospects Journal, 2016)
Scientific points of view as to the problem of self-realization and peculiarities of its development at the situation of family crisis were analyzed in the article. It was underlined, that studying of women’s problems at the crisis states and definition of predictors and preventers of personal lack of implementation and the family crisis as a factor of growth or deformation of women’s personal self-realization, is a necessary condition for psychocorrection and psychoprevention of mental and somatic health of  women, their development and self-realization. It was accented at the carrying out of analysis of interrelations between scales of self-actualization (competence at the time, scale of support, orientations of value, flexibility of behaviour, sensitiveness, spontaneity, self-respect, self-acceptance, ideas about the human nature, synergy, aggression acceptance, sociability, cognitive requirements, creativity) and at the dedicated block of family crisis which contains such factors as contentment by the marriage, styles of behaviour in conflict situations, orientations to the sex, love and sympathy, understanding, emotional attraction and authoritativeness. There were studied women at the age of 29-56 years and at the total quality 454 persons. Correlations were studied at the excerption which consists of 224 women from the crisis families and 104 of divorced women. The group of comparison consists of 126 women from ordinary families. There were defined direct, inverse and strong, weak correlations. The analysis of research results showed existence of considerable correlations in self-actualization with scales of family crisis block of studied women. Such interconnections at the group of women from ordinary families were less revealed than at the two crisis groups of women (crisis families and divorced). The largest quality of connections was revealed at the group of women from the crisis families. The analysis of connections at the group of women from the ordinary families allowed assuming of the existence of certain hidden problems, connected with self-realization and orientations to the sex.Key words: self-actualization, family crisis, contentment by the marriage, styles of behaviour at the conflict situations, orientations to the sex, love and sympathy, understanding, emotional attractiveness, authoritativeness.